Diagnostic Implications of p16 Expression in Serous Papillary Endometrial Cancer. Issue 8 (1st November 2011) - Netzer, Itamar M.; Kerner, Hedwiga; Litwin, Ludmila; Lowenstein, Lior; Amit, Amnon
Abstract : Objective: The purpose of this study was to examine whether the degree of expression of the p16 protein in serous papillary endometrial cancer bears a prognostic significance. The secondary objective was to establish the value of p16 immunohistochemical staining as an adjunct to diagnosis. Study Design: Archived paraffin blocks holding specimens from the uteri of 31 serous papillary and 31 endometrioid endometrial carcinoma patients were recut and restained for p16 and p53. Results: Overexpression of p16 was found in 78% of the serous papillary patients versus 36% of the endometrioid patients. p16 was not found to be an independent prognostic factor in serous papillary endometrial carcinoma. Conclusions: Although p16 was not found to have prognostic significance in serous papillary endometrial carcinoma, it may be valuable as a diagnostic adjunct in histologically ambiguous tumors.